CLUSTERING TECHNIQUE IN TEACHING WRITING DESCRIPTIVE TEXT FOR EFL CLASSES: IS IT EFFECTIVE? - linda septiyana; Sekar Ayu Anggraini (Universitas Pamulang, 2022)
In writing process there is a prewriting step. One of the prewriting steps is clustering. Clustering technique is a prewriting technique to produce ideas. The objective of the research is to find out whether there is a positive and significant effect of using clustering technique in teaching writing descriptive text for EFL classes at a secondary school. To collect the data the researchers used written test and observation. The researchers used quantitative research. This research used quasi experimental class with using experimental class and control class. The population of this research was all of the students in EFL classes at a secondary school, and the sample of this research is class IPA 2 and IPA 3. To analyze the data, the researchers used the formulation t-test. The result of this research show that df is 70 with t-table 5% is 1,667 with the t-observation is 12,1 it is mean that t-observation > t-table or it can be written 12,1>1,667. Therefore can be concluded that Ho is rejected. It means there is positive and significant, so the Clustering Technique was effective in teaching writing descriptive text on EFL classes at a secondary school.